Mathematical Model of Avian Inﬂuenza Epidemics with Vaccinating Poultry and Giving Treatment to Quarantined Infected Human - Kharis, Muhammad; Amidi, Amidi; Agoestanto , Arief (KnE Social Sciences, 2019)
Avian Inﬂuenza epidemics have an impact on human life both in the health and economic ﬁelds. This epidemic is one of major problem that causes the infected human get hospitalization. Some action are needed to prevent and reduce the impact of this outbreak. The actions which were done are vaccination in poultry, burning infected poultry, quarantining and giving treatment infected humans. Keywords: Avian Influenza; vaccination; Mathematical Model; Equilibrium Point; Stability